Mitogenome Analyses Reveal Limited Introduction of Anopheles coluzzii Into the Central African Islands of São Tomé and Príncipe - Ditter, Robert E.; Campos, Melina; Pinto, João; Cornel, Anthony J.; Rompão, Herodes; Lanzaro, Gregory C. (Frontiers in Tropical Diseases, 2022)
Islands possess physical characteristics that make them uniquely well-suited for initial field trials of new genetic-based technologies applied to African malaria vectors. This has led to efforts to characterize the degree of isolation of island mosquito populations. São Tomé and Príncipe (STP) is a country composed of two small islands in the Gulf of Guinea (West Africa) where Anopheles coluzzii is the primary malaria vector. Several studies have shown a relatively high degree of genetic isolation between A. coluzzii populations in STP and the mainland compared with pairs of mainland populations separated by equivalent distances. Here, we analyzed complete mitochondrial genomes of individual A. coluzzii specimens from STP and neighboring mainland countries. The objectives are to describe the history of A. coluzzii establishment in STP, specifically to address several questions germane to their suitability as sites for a field trial release of genetically engineered mosquitoes (GEMs). These questions include: (i) What are the origins of A. coluzzii populations in STP?; (ii) How many introductions occurred?; (iii) When was A. coluzzii introduced into STP? and (iv) Is there ongoing, contemporary gene flow into STP from mainland populations? Phylogenetic analysis and haplotype networks were constructed from sequences of 345 A. coluzzii from STP, and 107 individuals from 10 countries in West Africa. Analysis of these data suggest that there have been two introductions of A. coluzzii onto the island of São Tomé that occurred roughly 500 years ago and that these originated from west-central Africa. It appears that A. coluzzii has never been introduced into Príncipe directly from mainland Africa, but there have been at least four introductions originating from São Tomé. Our findings provide further support for the notion that contemporary populations of A. coluzzii on São Tomé and Príncipe are genetically isolated from mainland populations of this mosquito species.